Bibliometric Analysis of 14 Years of Research on Islamic Grameen Replicator Institutions in Indonesia - Fiqih Afriadi; Uswatun Chasanah (Universitas Alma Ata, 2025)
Introduction : This study examines the development of academic literature on Islamic Grameen Replicator institutions in Indonesia using a bibliometric analysis approach. The Islamic Grameen Replicator, which integrates Islamic finance principles with the Grameen model, has become increasingly relevant in efforts to empower low-income communities.Research Methods : The method employed in this study is a systematic literature review using VOSviewer software as the primary analytical tool. A total of 386 scholarly publications from 2009 to 2022 were collected from four major databases—Scopus, Google Scholar, CrossRef, and ProQuest—covering 21 Islamic Grameen Replicator institutions.Findings/Results : The results indicate a consistent upward trend in publications, with Micro Wakaf Bank (29%) and BTPN Syariah (18%) identified as the most frequently studied institutions. Airlangga University contributed the most to this body of work, and Jurnal Ekonomi Syariah Teori dan Terapan emerged as the most cited journal. Thematic analysis revealed four dominant areas of focus: financial services products, social performance, financial performance, and institutional management. Keyword co-occurrence analysis showed distinctive emphases across institutions, such as empowerment and qardhul hasan for BWM, and financial ratios and murabaha for BTPN Syariah.Conclusion : The study reveals a significant rise in literature on Islamic Grameen Replicators in Indonesia from 2009 to 2022, with BWM (29%) and BTPN Syariah (18%) as primary focuses. Research on BWM emphasized empowerment and qardhul hasan, while BTPN Syariah centered on financial ratios and murabaha financing, with financing-related topics dominating most publications.